(x+3)(x+1)=0

Simple and best practice solution for (x+3)(x+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+3)(x+1)=0 equation:


Simplifying
(x + 3)(x + 1) = 0

Reorder the terms:
(3 + x)(x + 1) = 0

Reorder the terms:
(3 + x)(1 + x) = 0

Multiply (3 + x) * (1 + x)
(3(1 + x) + x(1 + x)) = 0
((1 * 3 + x * 3) + x(1 + x)) = 0
((3 + 3x) + x(1 + x)) = 0
(3 + 3x + (1 * x + x * x)) = 0
(3 + 3x + (1x + x2)) = 0

Combine like terms: 3x + 1x = 4x
(3 + 4x + x2) = 0

Solving
3 + 4x + x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(3 + x)(1 + x) = 0

Subproblem 1

Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1

Solution

x = {-3, -1}

See similar equations:

| 17x=180 | | 10=-2c | | 6(5x+4)(3x-1)=0 | | v+42-3v=-34 | | 9g+8g=17 | | 8[5-3]=0 | | 3[2a-4]=0 | | 2c+a=-3c+44 | | 2z+5+3z=10 | | -5x^2+15x-9=0 | | -3[r+4]=21 | | -5w(w-3)(w+2)=0 | | -3[r+4]=-21 | | 5[q+6]=-20 | | 5[q+6]=20 | | 8x-9=33-4x | | 5x+7=2x-9 | | -3(-4-6x)=84 | | x^3+2x^2+4=0 | | -y+3z=9 | | 12+18x=84 | | 2+18x=84 | | 6x-6x=-2 | | 3x^3-6x^2-45x=0 | | 7k^2+6k-1=0 | | 5-(3n+5)=3-(7n+3) | | 14m+4n-6m+11n= | | 6n^2-14+8=0 | | 3(u-3)=2(x+5) | | [b+5]=2b+3 | | 15x^2-61x+53=-3 | | -2[5y-1]=-10 |

Equations solver categories